PERENCANAAN PAJAK PPH PASAL 21 SEBELUM DAN SESUDAH BERLAKUNYA PMK 66 TAHUN 2023 - Sinambela, Tongam; Reni Anggraeni (Jurnal Liabilitas, 2024)
The aim of this research is to determine the calculation of income tax article 21 based on the net, gross and gross up methods and the impact of implementing these methods after the enactment of PMK Number 66 of 2023. This research uses a qualitative descriptive method derived from a summary of the salary calculations for permanent employees in 2022 which was prepared by the author himself. The results of this research show that the gross method is more profitable in calculating PPh Article 21 payable and PPh Article 29 before and after the enactment of PMK Number 66 of 2023